POST-PANDEMIC TOURISM, PREPARATION IN TOURISM EDUCATION - Okky Rizal Ridwan; Diani Mustika Prianti (Program Pendidikan Vokasi, Universitas Indonesia, 2022)
ABSTRACTThe COVID-19 pandemic that spreads in Indonesia has changed the way people live their routines or the new normal. Consumers began to avoid physical contact with humans and switched to virtual or digital media. New lifestyle to stay at home with working-living-playing activities because of social restrictions is increasingly widespread. Similarly, tourists have complete awareness about cleanliness, health, safety, and environmental sustainability (CHSE). This awareness then affects the quality of service and products in the world of tourism in Indonesia. The purpose of this study is to align the change landscape COVID-19 in tourism education in order to deal with post-pandemic tourism. This research is a qualitative descriptive that uses books and other literature as the main object. The results showed that tourism education could effectively be done with industrial concept and new habits, creating innovative ideas, the use of technology, understanding of crisis management, and inculcating sustainable tourism principles. Suggestions for further research are to conduct quantitative research to find out the influence between post-pandemic tourism education preparation and contemporary issues that are developing in the world of tourism. Keywords: COVID-19, Post-Pandemic Tourism, Tourism Education